Missionale integriteit en kontekstuele relevansie - Nel, Malan (HTS teologiese studies, 2011)
Missional integrity and contextual relevanceThe research problem addressed in this article discussed whether so-called missional local churches too often escape local contextual involvement by sending money or even people to work on their behalf ‘elsewhere’. Is it true that local churches take the easier ‘money-way’ out to save a missional public face? The hypothesis is that missional integrity is in essence to be ‘firstly’ contextual relevant ‘before’ being nationally and even globally involved in mission. A basic assumption is that every local church is a gift of God to a specifically and even geographically defined context.